Analisis Lingkungan Internal Melalui Peran Sumber Daya Manusia Dalam Merencanakan Strategi Pemasaran Lembaga Pendidikan - Syarifah Nur Kholidah; Sultan Alawuddin Alislami; Hesti Kusumaningrum (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2024)
This research was conducted with the aim of analyzing the internal environment of educational institutions through the role of human resources in planning their marketing strategies. This type of research uses library research with the library study method. The research process was carried out by reviewing literature and analyzing topics relevant to the discussion as a data collection method. The findings of this study indicate that human resources play a crucial role in designing and implementing marketing strategies for educational institutions. With a deep understanding of an institution's internal strengths and weaknesses, human resources can identify opportunities and threats in the education market. An effective marketing strategy requires synergy between various departments within an educational institution. Human resources play an important role in facilitating various marketing ideas supported by the use of technology to make marketing strategies more effective. By using technology, human resources can improve their performance to carry out marketing optimally. The practical implications of these findings include the importance of human resource collaboration in planning marketing strategies by utilizing technology support to create creative marketing ideas, able to reach the wider community, and meet market needs.